Предмет: Алгебра,
автор: majapereverzeva
спростіть вираз (-⅔mn³)²×(3m²n)³=
Ответы
Автор ответа:
1
Ответ:
Объяснение:
*(-2/3 mn³)²=4/9 m²n^6
*(3m²n)³=27 m^6n³
(-2/3 mn³)² *(3m²n)³=4/9 m²n^6 * 27m^6n³=12m^8n^9
используем следующие формулы:
(а ^ к) ^ б = а ^ (к * б)
а ^ к * а ^ б = а ^ (к + б)
Похожие вопросы
Предмет: Математика,
автор: katya200v
Предмет: Математика,
автор: hadosha
Предмет: Математика,
автор: tttcoronavirus
Предмет: Английский язык,
автор: mariamgrigoryan458
Предмет: Алгебра,
автор: yevdokiyakomarova